# Which equation is in point-slope form and is depicted by the line in this graph? (y−3)=3/5(x−2)

Which equation is in point-slope form and is depicted by the line in this graph?

(y−3)=3/5(x−2)

(y−3)=−3/5(x+2)

(y−3)=5/3(x−2)

(y+3)=5/3(x+2)

$Which equation is in point-slope form and is depicted by the line in this graph? (y−3)=$

## This Post Has 9 Comments

1. jannaleigh says:

2. sarabell7626 says:

Step-by-step explanation:

Data

P (-2 , 3)

Q (3, 0)

Process

1.- Find the slope of the line

m = (0 -3) / (3 -(-2))

m = -3 / (3 + 2)

m = -3/5

2.- Find the equation of the line

Formula

y - y1 = m(x - x1)

Substitution

y - 3 = -3/5(x - (-2))

Simplification

y - 3 = -3/5(x + 2)

3. Sbudah2937 says:

The first thing you should do in this case is to write the equation in its generic form.
We have then:
y-yo = m (x-xo)
We look for the slope:
m = (y2-y1) / (x2-x1)
m = (0-3) / (3 - (- 2))
m = -3 / 5
We choose any point of the line:
(xo, yo) = (- 2, 3)
We substitute the values in the generic equation:
y-3 = -3 / 5 (x - (- 2))
We rewrite:
y-3 = -3 / 5 (x + 2)

b) (y - 3) = - 3/5 (x + 2)

4. lopez80 says:

5. mfin11 says:

$y-3=\frac{-3}{5}(x+2)$

Step-by-step explanation:

Points : (-2,3) and ( 3,0)

Let $(x_1,y_1)=(-2,3)$

$(x_2,y_2)=(3,0)$

Two point slope form : $y-y_1=\frac{y_2-y_1}{x_2-x_1}(x-x_1)$

Substitute the given points.

$y-3=\frac{0-3}{3-(-2)}(x-(-2))$

$y-3=\frac{0-3}{3+2}(x+2)$

$y-3=\frac{-3}{5}(x+2)$

Thus Option 2 is correct.

$y-3=\frac{-3}{5}(x+2)$ equation is in point-slope form and is depicted by the line in this graph

6. nurikchan says:

I hope this helps you
$Which equation is in point-slope form and is depicted by the line in this graph? the points are (-2$

7. smokey19 says:

The correct answer would be B.i hope that helped

8. look26goingjbgy says:

Y-y1=m(x-x1)
a point on the line is (x1,y1) and the slope is m

so
slope between (x1,y1) and (x2,y2) is (y2-y1)/(x2-x1)
so

points (-2,3) and (3,0)
slope is (0-3)/(3-(-2))=-3/(3+2)=-3/5
a point is (3,0) Or (-2,3)

so it could be
y-0=-3/5(x-3) or y-3=-3/5(x-(-2)) which is equal to y-3=-3/5(x+2)